Wind‐mediated horseweed (Conyza canadensis) gene flow: pollen emission, dispersion, and deposition. Issue 13 (17th June 2015) - Huang, Haiyan; Ye, Rongjian; Qi, Meilan; Li, Xiangzhen; Miller, David R.; Stewart, Charles Neal; DuBois, David W.; Wang, Junming
<x xml:space="preserve">Abstract</x> Abstract Horseweed (Conyza canadensis) is a problem weed in crop production because of its evolved resistance to glyphosate and other herbicides. Although horseweed is mainly self‐pollinating, glyphosate‐resistant (GR) horseweed can pollinate glyphosate‐susceptible (GS) horseweed. To the best of our knowledge, however, there are no available data on horseweed pollen production, dispersion, and deposition relative to gene flow and the evolution of resistance. To help fill this knowledge gap, a 43‐day field study was performed in Champaign, Illinois, USA in 2013 to characterize horseweed atmospheric pollen emission, dispersion, and deposition. Pollen concentration and deposition, coupled with atmospheric data, were measured in a source field (180 m by 46 m) and its surrounding areas up to 1 km downwind horizontally and up to 100 m vertically. The source strength (emission rate) ranged from 0 to 140 pollen grains per plant per second (1170 to 2.1×106 per plant per day). For the life of the study, the estimated number of pollen grains generated from this source field was 10.5×1010 (2.3×106 per plant). The release of horseweed pollen was not strongly correlated to meteorological data and may be mainly determined by horseweed physiology. Horseweed pollen reached heights of 80 to100 m, making long‐distance transport possible. Normalized (by source data) pollen deposition with distance followed a negative‐power exponential curve. Normalized pollen deposition was 2.5% even at 480 m downwind from the source edge. Correlation analysis showed that close to or inside the source field at lower heights (≤3 m) vertical transport was related to vertical wind speed, while horizontal pollen transport was related to horizontal wind speed. High relative humidity prevented pollen transport at greater heights (3–100 m) and longer distances (0–1000 m) from the source. This study can contribute to the understanding of how herbicide‐resistance weeds or invasive plants affect ecology through wind‐mediated pollination and invasion.